2017
DOI: 10.1186/s40348-017-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric precursor B acute lymphoblastic leukemia: are T helper cells the missing link in the infectious etiology theory?

Abstract: Precursor B acute lymphoblastic leukemia (BCP-ALL), the most common childhood malignancy, arises from an expansion of malignant B cell precursors in the bone marrow. Epidemiological studies suggest that infections or immune responses to infections may promote such an expansion and thus BCP-ALL development. Nevertheless, a specific pathogen responsible for this process has not been identified. BCP-ALL cells critically depend on interactions with the bone marrow microenvironment. The bone marrow is also home to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 93 publications
1
10
0
Order By: Relevance
“…The exact mechanisms of leukemic transformation through infection are not yet fully understood, but dysregulation of the immune system may play a major role. It has been proposed that memory T helper cells can support preleukemic B cell precursors in the bone marrow, and thus support ALL development [26].…”
Section: Mechanisms Of Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanisms of leukemic transformation through infection are not yet fully understood, but dysregulation of the immune system may play a major role. It has been proposed that memory T helper cells can support preleukemic B cell precursors in the bone marrow, and thus support ALL development [26].…”
Section: Mechanisms Of Transformationmentioning
confidence: 99%
“…Recent studies have shown that exposure to infection can trigger the progression from preleukemia to ALL [24,25]. A dysregulated immune response by activation of preleukemic B cells through memory T helper cells [26] and inactivity of NK cells have also been discussed [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to stromal cells, the immune microenvironment may also play an important role in the transition from pre-leukemia to leukemia. In particular, it has been proposed that memory T helper cells can support pre-leukemic BCP [ 54 ] and that Natural Killer (NK) cells with a low killing efficiency can confer a higher risk of ALL development by failing to clear pre-leukemic cells and early leukemic progenitors [ 5 , 55 ].…”
Section: The Role Of the Microenvironment In The Transition From Pre-leukemia To Overt Leukemiamentioning
confidence: 99%
“…High levels of IL-6 are thought to play a role in expression of let-7a [83]. In accord with the “Greaves hypothesis” of an infectious origin for BCP-ALL [82], Bürgler and Nadal [84] suggest that memory T-helper (Th) cells may be attracted by preleukaemic B-cells and can then be activated through presentation of antigens. BCP-ALL cells can also respond to Th cell cytokines [84].…”
Section: Microrna Biology and The Role In Cancermentioning
confidence: 99%
“…In accord with the “Greaves hypothesis” of an infectious origin for BCP-ALL [82], Bürgler and Nadal [84] suggest that memory T-helper (Th) cells may be attracted by preleukaemic B-cells and can then be activated through presentation of antigens. BCP-ALL cells can also respond to Th cell cytokines [84]. Correspondingly, miRNA have been shown to play a role in the regulation of cytokine genes and to be strongly regulated themselves during inflammation.…”
Section: Microrna Biology and The Role In Cancermentioning
confidence: 99%